High-voltage DC Converter System for Remotely Operated Vehicle and Its Control Strategy - CHEN Zhipeng (Kongzhi Yu Xinxi Jishu)
Working-class underwater vehicle require power supply devices that are high in power density, efficiency and redundancy. To meet these needs, this study designed a high-voltage DC converter system that operates with multiple converters running in parallel redundancy, intended for the power conversion and supply of remotely operated vehicle (ROV). Based on the analysis of the topology of multi-level flying capacitor Buck converters, a control method for the high-voltage DC converter system is proposed. This method integrates voltage equalization control for multiple devices connected in series inside the converter and current sharing control across multiple converters. Experimental verification was carried out to confirm the strategy's effectiveness. The results showed that the high-voltage DC conversion system and control strategy were both valid and reliable. Each flying capacitor voltage inside the converter remains stable, with a voltage deviation below 10%. The imbalance of output current across multiple converters is less than 5%, and the system demonstrated fast dynamic response. This system can be broadly applied to high-reliability required equipment in deep-sea environments, such as underwater vehicles.